IMPROVING THE QUALITY OF TRAINING FUTURE TEACHERS THROUGH COOPERATION BETWEEN UNIVERSITIES AND SCHOOLS - Gulmira Tojiboeva; Zilfira Dineeva; Nozima Rajabova (European Science Publishing, 2024)
This paper examines the pressing issue of improving the quality of education through effective interaction between higher education institutions (HEIs) and schools. Existing models of cooperation and their advantages are analyzed. Particular attention is paid to interaction mechanisms that promote the development of professional competencies of future teachers, the improvement of school programs and teaching methods, and the advanced training of current teachers.
Keywords: Higher education institutions, schools, cooperation, quality of education, teacher training, advanced training.